2013
DOI: 10.1212/wnl.0b013e31827deb99
|View full text |Cite
|
Sign up to set email alerts
|

Clinically feasible MTR is sensitive to cortical demyelination in MS

Abstract: Objective: Presently there is no clinically feasible imaging modality that can effectively detect cortical demyelination in patients with multiple sclerosis (MS). The objective of this study is to determine if clinically feasible magnetization transfer ratio (MTR) imaging is sensitive to cortical demyelination in MS.Methods: MRI were acquired in situ on 7 recently deceased patients with MS using clinically feasible sequences at 3 T, including relatively high-resolution T1-weighted and proton density-weighted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 19 publications
3
72
0
1
Order By: Relevance
“…Recent work has found that MTR is sensitive to cortical demyelination in patients with MS [38], and changes have been found in GM MTR and in the fornix specifically [39-41]. We did find modest positive correlations between MTR and performance on cognitive tasks, consistent with other studies that found associations between MTR and overall cognitive impairment [41-43].…”
Section: Discussionsupporting
confidence: 89%
“…Recent work has found that MTR is sensitive to cortical demyelination in patients with MS [38], and changes have been found in GM MTR and in the fornix specifically [39-41]. We did find modest positive correlations between MTR and performance on cognitive tasks, consistent with other studies that found associations between MTR and overall cognitive impairment [41-43].…”
Section: Discussionsupporting
confidence: 89%
“…For example, MT ratio (MTR) was shown to correlate well with myelin content in the white matter (Schmierer et al, 2004). Recently, MTR was shown to be sensitive to cortical demyelination in multiple sclerosis patients (Chen et al, 2013; Derakhshan et al, 2014). However, MTR is only a semi-quantitative metric and has several confounds.…”
Section: Discussionmentioning
confidence: 99%
“…MTR is an index calculated using images with and without MT saturation pulse and was shown to correlate with myelin content (Henkelman et al, 2001; Schmierer et al, 2004). Recently, MTR was mapped in the cortex of MS patients (Chen et al, 2013; Derakhshan et al, 2014) and showed similarities between myelinated regions and high MTR values. However, MTR is only a semi-quantitative metric as it depends on sequence parameters, B1 profile and T1 relaxation (Berry et al, 1999; Pike Bruce, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, we used a combination of MRI techniques: PSIR to detect cortical lesions, 15 high-resolution MTR (sensitive to GM demyelination), 16 and DTI to assess tissue structural integrity. To avoid contamination of GM lesion measures by WM, we confined our analysis to intracortical GM lesions.…”
Section: Introductionmentioning
confidence: 99%